Novel TREM2 splicing isoform that lacks the V‐set immunoglobulin domain is abundant in the human brain - Kiianitsa, Kostantin; Kurtz, Irina; Beeman, Neal; Matsushita, Mark; Chien, Wei‐Ming; Raskind, Wendy H.; Korvatska, Olena (Journal of leukocyte biology, 2021)
Triggering receptor expressed on myeloid cells 2 (TREM2) is an immunoglobulin‐like receptor expressed by certain myeloid cells, such as macrophages, dendritic cells, osteoclasts, and microglia. In the brain, TREM2 plays an important role in the immune function of microglia, and its dysfunction is linked to various neurodegenerative conditions in humans. Ablation of TREM2 or its adaptor protein TYROBP causes polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy (also known as Nasu‐Hakola disorder) with early onset of dementia, whereas some missense variants in TREM2 are associated with an increased risk of late‐onset Alzheimer's disease. The human TREM2 gene is subject to alternative splicing, and its major, full‐length canonic transcript encompasses 5 exons. Herein, we report a novel alternatively spliced TREM2 isoform without exon 2 (Δe2), which constitutes a sizable fraction of TREM2 transcripts and has highly variable inter‐individual expression in the human brain (average frequency 10%; range 3.7–35%). The protein encoded by Δe2 lacks a V‐set immunoglobulin domain from its extracellular part but retains its transmembrane and cytoplasmic domains. We demonstrated Δe2 protein expression in TREM2‐positive THP‐1 cells, in which the expression of full‐length transcript was precluded by CRISPR/Cas9 disruption of the exon 2 coding frame. Similar to the full‐length TREM2, Δe2 is sorted to the plasma membrane and is subject to receptor shedding. In “add‐back” experiments, Δe2 TREM2 had diminished capacity to restore phagocytosis of amyloid beta peptide and promote IFN‐I response as compared to full‐length TREM2. Our findings suggest that changes in the balance of two mutually exclusive TREM2 isoforms may modify the dosage of full‐length transcript potentially weakening some TREM2 receptor functions in the human brain. Graphical A novel TREM2 splicing isoform constitutes up to 35 percent of transcript repertoire in human brain and encodes protein with activities different from the canonic isoform